The place for Dry Land Agriculture in Kenya’s Secondary School Agriculture Curriculum - Miriam, Kyule, N.; Konyango, J. J. O. Jacob (Machakos University, 2019)
Purpose: The paper set out to document the extent to which secondary school agriculture curriculum addresses competencies on Dry Land Agriculture (DLA) and the possible ways of bridging the gaps. Approach: This is a historical paper based on desktop review of various education commission reports and policy documents as well as secondary school agriculture syllabus over time and other related research literature. Findings: The review revealed that soil and water conservation sub theme had the highest number of learning objectives addressing DLA while minimum soil disturbance had the least. Only 29.4 percent of the learning objectives focus on skill acquisition. Practical implication: To tap the agricultural potential in ASALs, learning objectives in the curriculum must focus more on competency acquisition since learning objectives inform the learning experiences that learners are subjected to. Learning objectives focusing on knowledge encourages theoretical implementation of the curriculum denying agriculture graduates the opportunity to learn through practice. Thus with few skills on DLA practices, secondary school graduates are less competent and lack the skill to transform the ASALs into food baskets. Theoretical implication: This study is informed by Competency based theory, Edgar dale and Kolb’s experiential learning theory. These theories emphasize on skill acquisition for various competencies through active participation of learners in related learning experiences; in this case, exposing agriculture students to DLA practices. Originality: The paper constitutes unique contribution towards the need to refocus agriculture curriculum content in Kenya secondary schools to address the societal needs in this case ASALs.
Keywords: Dry Land Agriculture; Agricultural education; Competency; Agriculture curriculum; Arid and Semi Arid Lands; Implementation.